(3GdHGchQI GdLfjI aj Yed GdBdI GdLjHjIs - (3eMeO Hf jhSa Hf YHO Gddg GdOeTbj, TeS GdOjf GdNjGW , GdVaOY,J (B756 (3g` s
(3ChdgG (B:s
(3MeOkG def CHOY ef MceJg eG LGQJ GdCacGQ ai UfYJg QaYgG SHYkG HZjQ YeO ehVMkG HgG SHjd GdegJOi SeJg GdHGchQI GdLfHI ai Yed ddBdI GdLjHjI s
(3BNQgG (B:s
(3OhQkG aeG aGb Hg agh GdCQH HdZJg CfJ hcd ef WdH hGdMeO ddg Ydi GdJeGe eG WdYJ PcG Ydi GdCfGe Ke GdUdGI hGdSdGe CHOkG JgOi dChL TeSg fhQ GdgOi s
(3CQLhRI ai GdejbGJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B153s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs